Pengaruh Sales Promotion, Live Streaming Shopping, dan Hedonic Consumption terhadap Impulse Buying pada E- Commerce Shopee - Putu Devyani; I Gusti Ayu Imbayani; Made Pradnyan Permana Usadi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the effect of sales promotion, live streaming shopping, and hedonic consumption on impulse buying in Shopee e-commerce. The rapid growth of e-commerce, supported by intensive promotional strategies and innovative features such as live streaming shopping, has influenced consumer behavior toward spontaneous purchasing decisions. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 162 respondents who are Shopee users in Denpasar City and have previously made purchases via live streaming shopping. The sampling technique used was purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that sales promotion, live streaming shopping, and hedonic consumption have a positive and significant effect on impulse buying. These findings suggest that more attractive sales promotions, higher interactivity in live streaming shopping, and stronger hedonic consumption motives increase consumers’ tendency to engage in impulsive buying behavior. This study is expected to contribute theoretically to marketing literature and provide practical insights for e-commerce businesses in developing effective marketing strategies.